Considering Interim Interventions to Control COVID-19 Associated Morbidity and Mortality—Perspectives - Arokiaraj, Mark Christopher (Frontiers in Public Health, 2020)
Aims and Objectives The pandemic of Covid-19 is evolving worldwide, and it is associated with high mortality and morbidity. There is a growing need to discuss the elements of a coordinated strategy to control the spread and mitigate the severity of Covid-19. H1N1 vaccine and streptococcus pneumonia vaccines are available. The current analysis was performed to correlate the severity of Covid-19 and influenza (H1N1) vaccination, lower respiratory tract infections (LRIs), and influenza attributable to lower respiratory tract infections’ incidence. Evolutionarily influenza is close to SARS-CoV-2 viruses and shares some common epitopes and mechanisms. Methods Recent influenza vaccination data of 34 countries from OECD and other publications were used to correlate with Covid-19 mortality from worldometer data. LRIs attributable to influenza and streptococcus pneumonia were correlated with Covid-19 mortality. Specifically, influenza attributable LRI incidence data of various countries (n=182) was correlated with Covid-19 death by linear regression and receiver operating characteristic (ROC) curve analyses. In a logistic regression model, population density and influenza LRI incidence were correlated with Covid-19 mortality. Results There is a correlation between Covid-19 related mortality, morbidity, and case incidence with the status of influenza vaccination, which appears protective. The tendency of correlation is more visualized as the pandemic is evolving. In countries where influenza immunization is less, there is a correlation between lower respiratory tract infections (LRI) and influenza attributable to LRIs incidence and Covid-19 severity, which is beneficial. ROC curve showed an area under the curve of 0.86 (CI 0.78 to 0.944, P <0.0001) to predict Covid-19 mortality >150/million, and a decreasing trend of influenza LRI episodes. To predict Covid-19 mortality of >200/million population the odds ratio for influenza incidence/100 000 was -1.86 (CI -2.75 to -0.96, P<0.0001). The predict the parameter - Covid-19 mortality/Influenza LRI episodes*1000 value>1000, the influenza LRI parameter had an odds ratio of -3.83 (CI -5.98 to -1.67), and an AUC of 0.94. Conclusion Influenza (H1N1) vaccination can be used as an interim measure to mitigate the severity of Covid-19. In appropriate high-risk circumstances, streptococcus pneumonia vaccination would also be an adjunct strategy, especially in countries with a lower incidence of LRIs.